2021
DOI: 10.1111/tpj.15129
|View full text |Cite
|
Sign up to set email alerts
|

Phaseolus vulgaris MIR1511 genotypic variations differentially regulate plant tolerance to aluminum toxicity

Abstract: The common-bean (Phaseolus vulgaris), a widely consumed legume, originated in Mesoamerica and expanded to South America, resulting in the development of two geographically distinct gene pools. Poor soil condition, including metal toxicity, are often constraints to common-bean crop production. Several P. vulgaris miRNAs, including miR1511, respond to metal toxicity. The MIR1511 gene sequence from the two P. vulgaris model sequenced genotypes revealed that, as opposed to BAT93 (Mesoamerican), the G19833 (Andean)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 74 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…Figure 5a shows a representative T plot (Addo‐Quaye et al., 2009) for legume‐specific miR2199 (Jagadeeswaran et al., 2009), that validates target homologues of helix‐loop‐helix DNA‐binding25‐like transcription factors (Figure S4; Supporting Information S4) previously identified only in Medicago truncatula (Devers et al., 2011; Fei, Wang et al., 2018). Figure 5b (see also Figure S4) shows support for a novel Exocyst complex sec15A noncanonical target sliced by miR1511, a legume‐validated miRNA recently shown to canonically target ABC transporter‐like Aluminum Sensitive Protein3 transcripts (validated in Supporting Information S4) which function in aluminum detoxification and phosphate/reactive oxygen signaling associated with evolved drought/soil acidity tolerances in bean (Martín‐Rodríguez et al., 2021). Evidence for targets of miR530 have been varied in the literature; for example, predicted miR530 target ARGONAUTE1 (Shao & Lu, 2013; Sunitha et al., 2019) has not been established experimentally.…”
Section: Resultsmentioning
confidence: 81%
“…Figure 5a shows a representative T plot (Addo‐Quaye et al., 2009) for legume‐specific miR2199 (Jagadeeswaran et al., 2009), that validates target homologues of helix‐loop‐helix DNA‐binding25‐like transcription factors (Figure S4; Supporting Information S4) previously identified only in Medicago truncatula (Devers et al., 2011; Fei, Wang et al., 2018). Figure 5b (see also Figure S4) shows support for a novel Exocyst complex sec15A noncanonical target sliced by miR1511, a legume‐validated miRNA recently shown to canonically target ABC transporter‐like Aluminum Sensitive Protein3 transcripts (validated in Supporting Information S4) which function in aluminum detoxification and phosphate/reactive oxygen signaling associated with evolved drought/soil acidity tolerances in bean (Martín‐Rodríguez et al., 2021). Evidence for targets of miR530 have been varied in the literature; for example, predicted miR530 target ARGONAUTE1 (Shao & Lu, 2013; Sunitha et al., 2019) has not been established experimentally.…”
Section: Resultsmentioning
confidence: 81%
“…Therefore, for this study, the two contrasting genotypes L‐4602 and BM‐4 were chosen at the seedling stage for proteomic analysis in response to Al stress under hydroponic conditions. A similar configuration of root morphological traits was also used to substantiate Al tolerance in Phaseolus vulgaris (Blair et al, 2009; López‐Marín et al, 2009; Ángel Martín‐Rodríguez et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for this study, the two contrasting genotypes L-4602 and BM-4 were chosen at the seedling stage for proteomic analysis in response to Al stress under hydroponic conditions. A similar configuration of root morphological traits was also used to substantiate Al tolerance in Phaseolus vulgaris(Blair et al, 2009;López-Marín et al, 2009;Ángel Martín-Rodríguez et al, 2021).4.1 | Physiological transition in response to Al stressIn this study, we have phenotyped traits such as relative root elongation, Al contents, morin score, root tolerance index, callose deposition and Al localization in root apex in Al-tolerant (L-4602) and Al-sensitive (BM-4) genotypes of lentil at different time intervals (0, 3, 6 12 and 24 h) to determine the best time for further analyses. We observed that Al exposure of 6 h was the most effective time for differentiating Al response as significant harmful effects of Al were noted in the Al-sensitive genotype (BM-4), with lower root tolerance index, increased Al accumulation and bioaccumulation factor, higher deposition of callose and disrupted malate secretion than in the Al-tolerant genotype (L-4602).…”
mentioning
confidence: 99%
“…Another miRNA named miR1511 for the MIR1511 gene responded against Al toxicity in common bean and then targeted against ALS3 ( Aluminum Sensitive Protein 3 ) gene. Both the genes opposed each other for sensitive genotypes as decreased expression of miR1511 showed increased ALS3 transcript level under Al toxicity and vice versa, thus revealing the prominent role of miR1511 for inducing resistance against Al stress in plants ( Ángel et al, 2021 ). Overexpression of miR156 had significantly reduced the endogenous ROS in Arabidopsis and enhanced tolerance against Cd stress by reducing the effect of Cd-related transporters ( Zhang et al, 2020c ).…”
Section: Seven-(omics)-based Approaches To Improve Toxic Metals/metalloids Tolerance In Plantsmentioning
confidence: 99%